Physical Characteristics, Moisture Content and Organoleptic Properties of Afkir Laying Hen Meat with Different Marination Durations in Pineapple Crown Extract - Siti Susanti; Heni Rizqiati; Marwa Syifa Adlina (Sam Ratulangi University, 2024)
Afkir laying hen meat has a tough texture, making it less desirable to consumers. Pineapple crown extract is known to improve the texture of spent laying hen meat due to its bromelain enzyme content. This study aims to determine the effect of marination duration using pineapple crown extract on the pH, cooking loss, water content, water holding capacity, texture, and organoleptic value of spent laying hen meat. The study was conducted using a Completely Randomized Design with 4 treatments (different marination times of 0, 2, 4, and 6 hours) and 5 replications. The parameters observed in this study included pH, cooking loss, water content, water holding capacity, texture, and organoleptic values. Test data were analyzed statistically using Analysis of Variance with a 5% significance level, and if significant effects were found, the analysis was followed by Duncan’s Multiple Range Test. Organoleptic test data were analyzed with the Kruskal-Wallis method, and if there were significant effects, further analysis was conducted using the Mann-Whitney test. The results showed a significant effect (P<0.05) of marination time using pineapple crown extract on the pH, water content, and organoleptic parameters, including taste, texture, color, and overall preference, with no significant effect (P>0.05) on cooking loss, water holding capacity, or the aroma attribute in the organoleptic test. Marination time also decreased the toughness of afkir laying hen meat texture, as analyzed descriptively. Marination for 2-6 hours decreased pH and water content, tenderized the texture, and improved meat preference. Keywords: Afkir laying hen; bromelain; tenderness; pineapple crown; marination